Social Accounting Matrix for India 2017-18 - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
Social Accounting Matrix for India 2017-18 accounts 112 sectors of Indian economy of which 39 sectors are accounted for agriculture and allied activities, 18 sectors are related to agriculture-based processing activities, 4 mining sectors, 24 manufacturing sectors other than agro-processing, 3 sectors related to utilities, 1 construction sector and 23 service sectors including transport and trade. The primary factor input has been classified into 8 types of labor, 4 types of capital, and one category of land. The categorization of labor is based on the level of education of the workers and geographical location i.e. rural and urban. The 4 types of capital are; crop, live animal, mining, and other financial capital. This SAM distinguishes households into three broad categories like rural farm households, rural non-farm households, and urban households. Households are further disaggregated into per capita expenditure quintiles. Therefore, this database is useful for scholars and policymakers who are interested to work on macroeconomic policy analysis for the Indian economy.